Enhanced Efficiency of a Novel Porous Tip Irrigated RF Ablation Catheter for Pulmonary Vein Isolation. (25th July 2013) - PARK, CHAN‐IL; LEHRMANN, HEIKO; KEYL, CORNELIUS; WEBER, REINHOLD; SCHURR, PATRICK; SCHIEBELING‐RÖMER, JOCHEN; ALLGEIER, JUERGEN; HERRERA, CLAUDIA SIKLODY; KIENZLE, ROLF‐PETER; SHAH, DIPEN; NEUMANN, FRANZ‐JOSEF; ARENTZ, THOMAS; et al.
Enhanced Efficiency of a Novel Porous Tip Irrigated RF Ablation Catheter Introduction Irrigated tip radiofrequency (RF) catheter ablation is the most frequently used technology for pulmonary vein isolation (PVI). The purpose of this study was to compare the efficiency and the safety of 2 different open irrigated tip RF ablation catheters. Methods and Results A total of 160 patients with symptomatic AF (29% persistent, 68% male, 61 ± 10 years) were randomized to circumferential PVI using 2 different irrigated tip catheters: (1) the novel Thermocool SF® with a porous tip (56 holes) or (2) the Thermocool® catheter with 6 irrigation holes at the distal tip in both power‐ and temperature‐controlled modes. PVI procedural time and RF duration were significantly shorter with SF® versus Thermocool® catheter: 104.5 versus 114 minutes (P = 0.023) and 35.4 minutes versus 39.9 minutes (P < 0.001), respectively. Similarly, the total fluoroscopy time and dose were shorter with SF® versus. Thermocool® catheter: 21 minutes versus 24 minutes (P = 0.02) and 1014.5 μGy*m2 versus 1377 μGy*m2 (P < 0.0001), respectively. Irrigation volume was lower with SF®: 600 mL versus 1100 mL, (P < 0.0001) and the rates of complications were not significantly different (0.6% vs 0.49%, P = 0.66). At 20.5 ± 7.5 months follow‐up, there were no significant differences with regard to arrhythmia freedom between SF® (59.2%) and TC® groups (59.3%), (P = 0.61). Conclusions Using the novel irrigated tip SF catheter, PVI is achieved within a shorter ablation and procedural durations. The underlying mechanisms and potential differences in RF lesion size remain to be elucidated.